Characterization of viral proteases from Norwalk virus, poliovirus, and transmissible gastroenteritis virus using a fluorescence resonance energy transfer assay - Pasupulleti, Venkata Kiran (Kansas State University, 2012)
Positive sense RNA viruses include diverse groups of viruses that cause a wide variety of diseases in humans and animals. Most of these viruses encode proteases that cleave the viral polyprotein into intermediate or mature functional proteins during virus replication. As these proteases play a critical role in virus replication, they represent an attractive target for the development of antiviral drugs. In this study, the main goal was to establish assay systems and characterize the enzymatic activity of related proteases from Norwalk virus (NV), poliovirus, and transmissible gastroenteritis virus (TGEV). These proteases share several common characteristics including a typical chymotrypsin-like fold, a Cys residue as a nucleophile in the catalytic triad (or dyad) composed of Cys, His and Glu (or Asp) residues, and a preference for a Glu or Gln residue at the P1 position on the substrate. We cloned and expressed proteases from these viruses and characterized their enzymatic activities using a fluorescence resonance energy transfer (FRET) assay using a specific FRET substrate corresponding to each viral protease. First, assay conditions of the FRET assay was optimized for each virus protease. Second, inhibition profiles of each virus protein were investigated using five commercially available standard protease inhibitors (chymostatin, leupeptin, antipain, TPCK, and TLCK). The inhibition studies showed that TPCK inhibited NV, poliovirus, and TGEV proteases with varying strength, and chymostatin inhibited only NV protease. All other inhibitors had little effects on the virus proteases. The established FRET assays should facilitate screening potential antivirals.
Keywords: Proteases; FRET assay; Virology (0720)